Scaling fashion rental services - A case study on a sustainability transition in the Swedish fashion industry - Weitekamp,Johanna (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
The global fashion industry causes severe environmental and social harm, underscoring the urgent need for a sustainability transition. Circular Business Models, such as Fashion Rental Services (FRS), represent a promising yet currently limited alternative with reduced environmental impacts. This study presents a case study of the fashion industry’s sustainability transition by exploring FRS in Sweden through the Multi-Level-Perspective framework. It draws on semi-structured interviews with practitioners and experts, alongside an analysis of the EU Textile Strategy’s role as a transition driver. Findings highlight barriers and drivers to scaling FRS. The latter includes shifting consumer norms, business model innovation, and regulatory support. While the Textile Strategy plays a significant role, its full impact remains uncertain. This study identifies implications for EU and Swedish national policy, compromising binding regulations, fiscal tools, and support for innovation. This study offers a minor, yet meaningful contribution to the sustainability transition of the fashion industry.
Keywords: Sustainability Science; Fashion Industry; Fashion Rental Services; EU Textile Strategy; Multi-Level-Perspective